Another Look at Governments' Balance Sheets : The Role of Nonfinancial Assets - Bova, Elva (IMF Working Papers; Working Paper ;, 2013)
When discussing debt reduction strategies, little attention has been given to the role of governments' nonfinancial assets. This is in part because data are scarce. Drawing on various data sources, this paper looks at the size, composition, and management of state-owned nonfinancial assets across 32 economies, with particular focus on the advanced G-20 economies. We find that reported nonfinancial assets comprise mostly structures (such as roads and buildings) and,when valued, land. These assets have increased over time, mostly due to higher property and commodity prices, and are, in large part, owned by subnational governments. Many countries have launched reforms with a view to streamlining public administrations, but receipts and savings have been rather small so far. Governments tend to consider relatively small sets of assets to be disposable, though preferences could change in the future. A potential source for future revenues could be greater reliance on user charges, such as road tolls. In most cases, a first step for more effective asset management has to be the expansion and improvement of data compilation.